2012
DOI: 10.1155/2012/686153
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Inflammation in Pulmonary Granuloma 48 Years after Talcage Pleurodesis, Detected by FDG-PET/CT

Abstract: In patients with suspicion of lung malignancy, FDG PET/CT is frequently used as a diagnostic and staging imaging modality. However, false positive findings are not uncommon. We demonstrate a case with FDG-avid pulmonary nodules, mimicking lung cancer. After histopathological examination they appeared to be the result of persistent inflamed tissue, due to talcage pleurodesis, which occurred 48 years ago. We concluded that, nearly five decades after talcage pleurodesis, there can still be an ongoing inflammation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…3 ). Pleurodesis with inflammation-inducing agents, such as OK-432 or talc, results in high FDG uptake [ 8 , 9 ] (Fig. 4 ).…”
Section: Invasive or Surgical Proceduresmentioning
confidence: 99%
“…3 ). Pleurodesis with inflammation-inducing agents, such as OK-432 or talc, results in high FDG uptake [ 8 , 9 ] (Fig. 4 ).…”
Section: Invasive or Surgical Proceduresmentioning
confidence: 99%
“…Markedly increased FDG uptake characterizes the process, which can persist for an unpredictable period ( Figure 7 ). 100 102 Several authors 103 106 have reported the presence of focal and/or diffused tracer accumulation visible on partially calcified pleural thickening years (up to decades) following pleurodesis. Since only 10% of pleural malignancies present with calcifications, major help in the identification of these cases is given by proper anamnesis and by the identification on CT images of concordance/overlap between FDG-avid lesions and highly CT-attenuated areas.…”
Section: Metabolic Imagingmentioning
confidence: 99%
“…Since only 10% of pleural malignancies present with calcifications, major help in the identification of these cases is given by proper anamnesis and by the identification on CT images of concordance/overlap between FDG-avid lesions and highly CT-attenuated areas. 99 , 104 106 The negative impact of FDG uptake induced by pleurodesis is seen at initial staging, as well as at response assessment, since the effective extent of MPM can be overestimated by the contemporary presence of pleural granulomatous reaction to talc.…”
Section: Metabolic Imagingmentioning
confidence: 99%
“…1,4,5 It is well established, 6-20 that talc deposits in the pleura produce areas of increased 18 F-FDG uptake, for up to 48 years after the performance of TP. 18 Distinguishing pleural malignancy from talc-induced benign inflammatory changes is challenging by 18 F-FDG, especially in patients with history of both thoracic malignancy and TP. This diagnostic dilemma becomes even greater, when pulmonary parenchymal nodules develop because of talc-particle absorption through the pleura, with avid 18 F-FDG uptake.…”
Section: Figurementioning
confidence: 99%